PITPs as targets for selectively interfering with phosphoinositide signaling in cells - Nile, A.; Tripathi, A.; Yuan, P.; Mousely, Carl; Suresh, S.; Wallace, I.; Shah, S.; Pohlhaus, D.; Temple, B.; Nislow, C.; Giaever, G.; Tropsha, A.; et al. (Nature Publishing Group, 2014)
Sec14-like phosphatidylinositol transfer proteins (PITPs) integrate diverse territories of intracellular lipid metabolism with stimulated phosphatidylinositol-4-phosphate production and are discriminating portals for interrogating phosphoinositide signaling. Yet, neither Sec14-like PITPs nor PITPs in general have been exploited as targets for chemical inhibition for such purposes. Herein, we validate what is to our knowledge the first small-molecule inhibitors (SMIs) of the yeast PITP Sec14. These SMIs are nitrophenyl(4-(2-methoxyphenyl)piperazin-1-yl)methanones (NPPMs) and are effective inhibitors in vitro and in vivo. We further establish that Sec14 is the sole essential NPPM target in yeast and that NPPMs exhibit exquisite targeting specificities for Sec14 (relative to related Sec14-like PITPs), propose a mechanism for how NPPMs exert their inhibitory effects and demonstrate that NPPMs exhibit exquisite pathway selectivity in inhibiting phosphoinositide signaling in cells. These data deliver proof of concept that PITP-directed SMIs offer new and generally applicable avenues for intervening with phosphoinositide signaling pathways with selectivities superior to those afforded by contemporary lipid kinase–directed strategies.